Antimicrobial and Substantivity Properties of Silver Nanoparticles against Oral Microbiomes Clinically Isolated from Young and Young-Adult Patients. (30th November 2019) - Espinosa-Cristóbal, León Francisco; Holguín-Meráz, Carolina; Zaragoza-Contreras, Erasto Armando; Martínez-Martínez, Rita Elizabeth; Donohue-Cornejo, Alejandro; Loyola-Rodríguez, Juan Pablo; Cuevas-González, Juan Carlos; Reyes-López, Simón Yobanny
Abstract : The dental plaque is an oral microbiome hardly associated to be the etiological agent of dental caries and periodontal disease which are still considered serious health public problems. Silver nanoparticles (AgNPs) have demonstrated to have good antimicrobial properties affecting a wide variety of microorganisms, including oral bacteria; however, there is no scientific information that has evaluated the antimicrobial effect of AgNPs against clinical oral biofilms associated with dental caries and periodontal disease. The aim of this study was to determine the antimicrobial and substantivity effects of AgNPs in oral biofilms isolated clinically from patients with dental caries and periodontal disease. Sixty-seven young and young-adult subjects with dental caries and periodontal disease were clinically sampled through the collection of subgingival dental plaque. The inhibitory effect of AgNPs was performed with standard microbiological assays by triplicate using two sizes of particle. Polymerase chain reaction (PCR) assay was used to identify the presence of specific bacterial species. All AgNPs showed an inhibitory effect for all oral biofilms for any age and, generally, any gender (p > 0.05 ); however, the effectiveness of the antimicrobial and substantivity effects was related to particle size, time, and gender (p < 0.05 ). The identified microorganisms were S. mutans, S. sobrinus, S. sanguinis, S. gordonii, S. oralis, P. gingivalis, T. forsythia, and P. intermedia . The AgNPs could be considered as a potential antimicrobial agent for the control and prevention of dental caries and periodontal disease.